Development of Student Associations Information System at Universitas Pembangunan Nasional Veteran Jakarta - Adrezo, Muhammad; Wirawan, Rio (JISA(Jurnal Informatika dan Sains), 2021)
Universitas Pembangunan Nasional Veteran Jakarta (UPN Veteran Jakarta) is one of the public universities which views student associations to play an important role in student self-development. Student’s self-development can be realized if students participate in every activity. but a lot of problems that occur because the process related to student association is still done manually without using an information system, where students have to come to campus to take care of all the needs to hold an activity. So that we need a system that aims to improve services to student associations as well as facilitate the management of existing student associations data and can increase the credibility of UPN Veteran Jakarta itself. It is called SIWA. It is expected to minimize errors that occur and manage business processes that exist in each student association. So that the benefits generated later, it is hoped that information on Real Estimate of Cost, submission of activity proposals, accountability reports and annual reports can be managed properly. Besides that, it can also support a paperless culture in the college environment. This information system will be built based on a web-based system and its development will use the waterfall method.